Analisis Framing Pemberitaan Film Dokumenter Dirty Vote Pemilu 2024 di Media Online iNews.id dan Viva.co.id - Rizki, Dina Setya Nur; Candrasari, Yuli (Universitas Batanghari Jambi, 2024)
Reporting on online media in the political year creates momentum to highlight political interests. One of the news stories that is an important and current focus is the case of the dirty vote documentary film. The method that will be used in this research is framing analysis using the theoretical device model of Zhongdang Pan and Gerald M. Kosicki. The results of the research reveal that in writing news related to the dirty vote film on iNews.id and viva.co.id there are several differences and similarities in framing the news writing. In the syntactic aspect of the iNews.id media, writing framing news with words that have a peaceful nuance does not trigger the reader's annoyance. Meanwhile, at viva.co.id, when writing headlines, they use words that show the problem in the writing and use interrogative sentences as headlines. In the script aspect, both media fulfill the 5W + 1H rule in writing their news. In the thematic aspect, in general, the writing of sentences in conveying news in the two media is related to each other and does not have a fixed number of paragraphs in each news. In the rhetorical aspect, viva.co.id uses more metaphors and words with negative connotations or that cause a response from the reader. Meanwhile, iNews.id is more inclined towards conveying positive sentences related to this news.